1990
DOI: 10.1161/01.res.66.5.1328
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and particulate depositions for regional myocardial flows in sheep.

Abstract: The deposition of microspheres in small tissue regions is not strictly flow dependent. In comparison with the soluble flow marker 2-iododesmethylimipramine (IDMI), deposition of 16.5-,um microspheres was mildly but systematically biased into high flow regions of rabbit hearts (Bassingthwaighte JB, Malone MA, Moffett T-C, King RB, Little SE, Link JM, Krohn KA. Am J Physiol 1987;253(Heart Circ Physiol 22):H184-H193). To examine the possibility of bias in larger hearts, a similar study was undertaken in sheep. 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
59
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 33 publications
4
59
0
1
Order By: Relevance
“…This has profound consequences for the spatial scale where microsphere can be a valid means to test the local perfusion. Previous studies supported the validity of microsphere flow determinations down to 200 mg in larger animals (3,16) and 50 mg in smaller animals (4). The present data indicate that at a spatial scale Ͻ2 mg ( l) local flow may not be the dominant force governing microsphere deposition.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This has profound consequences for the spatial scale where microsphere can be a valid means to test the local perfusion. Previous studies supported the validity of microsphere flow determinations down to 200 mg in larger animals (3,16) and 50 mg in smaller animals (4). The present data indicate that at a spatial scale Ͻ2 mg ( l) local flow may not be the dominant force governing microsphere deposition.…”
Section: Discussionsupporting
confidence: 85%
“…This is supported by the fact that multiple injections of FMS resulted in stacking of spheres in the same vessel implying that although the MS was "trapped", the flow, or delivery of spheres, was not reduced to zero in the vessel. These streaming artifacts were previously recognized in rather large areas of high flow, ranging from 1 to 0.25% of left ventricular mass (3,4), and are consistent with in vitro experiments demonstrating a bias of spherical particles at branch points toward the higher flow branch (7). Consequently, for small individual sample sizes, supplied by small arteriolar vessels, microspheres will not represent a valid means for flow determinations.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, when analysis of the local deposition density of microspheres [2][3][4][5] and diffusible plasma flow markers [6][7][8] in volume elements of a few millimeters diameter showed that the local flow distribution within individual hearts is markedly heterogeneous, covering a range from 20% to 200% of the mean value. This flow heterogeneity is remarkably stable over periods of several hours, 4 even if the heart is intermittently stimulated.…”
mentioning
confidence: 99%